AUDIT CERTIFICATES AND REPORTS. - Jackson, J. Hugh (The Accounting Review, 1926)
Abstract At the annual meeting of the American Association of University Instructors in Accounting in Pittsburgh in 1921, one of the prominent accountants of the U.S. read a paper entitled "The Need of a Broader Conception of the Work of the Accountant." Early in his discussion this accountant stated that all of his firm's work was built about its annual and periodical audits. He proceeded to say that practically all of the work done in constructive accounting, public utility accounting, tax work and industrial engineering, resulted directly or indirectly from these audits. A partner in another accounting firm, which does work of an entirely different nature, and the partners of which, presumably, have little interest in the auditing aspect of accountancy, recently stated that it was a real problem whether or not the auditing work would largely supersede the other accounting activities in which the firm was more interested. These two examples, taken from the experience of firms who are not primarily interested in auditing, tend to emphasize the importance in the work of almost every accountant of the annual or periodic audit. The constructive audit is and probably will continue to be, the most important part of the public accountant's work.